Saberes experienciais dos professores de ciências e biologia do município de Aracaju: indícios de concepções sobre a aprendizagem dos alunos - Santos-galvão, Luzia Cristina de Melo (2013)
With the passing of time society has been transforming. This transformation, in most cases, is given by advancements and changes taking place as in ambit political as in technological, year after year, with great reflexes also in the educational field. Today, the teachers, when well advised, can rely on a technical and methods apparatus that may be used to assist their work on development of their classes and, in consequence, to facilitate the learning process of their students, particularly, in science education and biology. The research presented here has as objective unveiling the experiential knowledge of teachers of Science and Biology, two schools in the state education network in the city of Aracaju-Sergipe, through the evidence of conceptions about the student learning. How problematic we have the following questions: which teachers' conceptions of science and biology in relation: previous knowledge of the students; experimental activities, the use of educational games and audiovisual resources; research content in the classroom, the students' errors, and the evaluation process in the classroom, all these questions related to the student learning? Will teachers believe that for students to learn science and biology is necessary to adopt techniques and methods in their pedagogical practice? As a theoretical reference, we seek for broach the main theorists who talk so much about the process of student learning, how much the assumptions presented above, citing authors like: Vigotskii, Libâneo, Perrenould, Luckesi, among others. Concerning the nature and techniques of data collection, the research has a qualitative approach with phenomenological focus, using how instruments interviews, questionnaires and observations, having as contributions theoretical, authors as: Gil (1996), Laville and Dionne (1999), Milk (1999) and Triviños (1999). We found that teachers are aware of the need to innovate the way develop their lessons, by the use of methods and techniques different of traditional. However, we found some difficulties, such as: lack of materials, short class time assigned to disciplines, especially biology, lack of support at the time of development of their activities. Something extremely important was the similarities of the conceptions of teachers on research environments. Despite some differences in the physical aspect of the two schools, respondents forwarded the same difficulties earlier said.